Efficient Decentralisation with a Transferable Good - Browning, M. J. (Review of Economic Studies, 1983)
There are many situations where agents supply input factors and produce a transferable good (money). This paper examines the conditions on technology under which agents can specify reward schedules which lead to an efficient outcome even if inputs are chosen non-cooperatively and preferences are private information. The characterisation of the class of technologies that allows this involves a generalization of additivity known as (n − 1)-additivity.